Features of the legal status of subjects of copyright in the audiovisual work - Шуст, Наталія Борисівна; Дробович, Тетяна Миколаївна; Мельник, Павлина Михайлівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The production process and the use of audiovisual works is a complex legal structure. Civil, labor and copyright relationships that accompany the process of creation and use of audiovisual works, often closely intertwined, requiring serious legal support. The situation is complicated by the fact that every new project is a unique and unprecedented case. One or a group of writers, using previously established copyright, the director and his authority, a combination of several copyright powers in a single person, the relationship with the technical staff and a group of actors and other large and small details combine to create many variations for which it is impossible to produce single algorithm. All this points to the relevance of the research topic. The purpose of this article is to identify the characteristics of civil relations involving of intellectual property rights in the audiovisual work based on comparative analysis of the legislation of Ukraine, foreign countries and international treaties, and to obtain opinions and formulation offerings, aimed at improving civil legal regulation of these relations and laws of Ukraine accordance with generally accepted international standards. This article examining the subject of legal regulation of relations on the creation, use and protection of audiovisual work, as the object of intellectual property, we noticed a cinematographic work, which includes audiovisual work.